2023
DOI: 10.1186/s12935-023-03009-2
|View full text |Cite
|
Sign up to set email alerts
|

Xanthohumol hinders invasion and cell cycle progression in cancer cells through targeting MMP2, MMP9, FAK and P53 genes in three-dimensional breast and lung cancer cells culture

Abstract: Background Despite recent advances in the treatment of lung and breast cancer, the mortality with these two types of cancer is high. Xanthohumol (XN) is known as a bioactive compound that shows an anticancer effect on cancer cells. Here, we intended to investigate the anticancer effects of XN on the breast and lung cancer cell lines, using the three-dimensional (3D) cell culture. Methods XN was isolated from Humulus lupulus using Preparative-Thin L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 39 publications
1
0
0
Order By: Relevance
“…Several studies have demonstrated the anti-cancer e cacy of XN. XN has been shown to promote apoptosis [12], inhibit tumor invasion [13], cell cycle progression [13], and reduce in ammation and cell metabolism [14]. These ndings together with our results show that XN has anti-tumor effects.…”
Section: Discussionsupporting
confidence: 83%
“…Several studies have demonstrated the anti-cancer e cacy of XN. XN has been shown to promote apoptosis [12], inhibit tumor invasion [13], cell cycle progression [13], and reduce in ammation and cell metabolism [14]. These ndings together with our results show that XN has anti-tumor effects.…”
Section: Discussionsupporting
confidence: 83%